Pulmonary hypertension is not a risk factor for grade 3 primary graft dysfunction after lung transplantation. Issue 5 (30th April 2018) - Cottini, Silvia R.; Brandi, Giovanna; Pagnamenta, Alberto; Weder, Walter; Schuepbach, Reto A.; Béchir, Markus; Huber, Lars C.; Benden, Christian
Abstract: Grade 3 primary graft dysfunction (PGD3) represents the most important risk factor for patient mortality during the first year after lung transplantation (LTX). We investigated whether pretransplant pulmonary hypertension (PH) is a risk factor for the development of PGD3. This retrospective, single‐center cohort study included 96 candidates undergoing right heart catheterization (RHC) prior to being listed for LTX between March 2000 and October 2015. Based on their mean pulmonary artery pressure (mPAP) levels, the patients were classified into 3 groups: (1) <25 mm Hg, (2) 25‐34 mm Hg and (3) ≥35 mm Hg. Forty‐seven patients were classified in group 1, 31 in group 2, and 18 in group 3. Fifteen recipients (16%, 95%‐CI 8‐23) developed PGD3. In the univariate analysis, the diagnosis of interstitial lung disease (ILD) compared to COPD (OR: 7.06, P = .005), blood transfusion >1000 mL during surgery (OR: 5.25, P = .005), the need for intra‐operative cardio‐pulmonary bypass (CPB) or extra‐corporeal membrane oxygenation (ECMO) (OR: 4, P = .027), mPAP (OR 1.06, P = .007) and serum high density lipoprotein‐cholesterol (HDL‐C) (OR 0.09, P = .005) were associated with PGD3. In the multivariable logistic regression analysis, only HDL‐C (OR 0.10, P = .016) was associated with PGD3 based on our single‐center cohort data analysis.